Necrotising Fasciitis following Intramuscular Injection in a Nigerian Neonate: A case report - Ogundele T; Egwumah-Atule E; Osundare YJ; Oyelami O (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2022)
Necrotizing fasciitis (NF) is a rare but severe, life-threatening bacterial infection of the fascia, with secondary necrosis of the subcutaneous tissues. Necrotizing fasciitis is caused by an infection of the skin, subcutaneous tissue, and fascia by one or more bacterial organisms, resulting in the death of these tissues. NF is rare in neonates, but it has been reported following omphalitis, balanitis, mastitis, and postoperative complications. The mortality in neonates with necrotizing fasciitis has been reported to be as high as fifty per cent. We report a case of NF in a term male neonate with an intramuscular injection at the left shoulder at birth under suspected septic conditions. The wound swab yielded Escherichia coli and Pseudomonas species, while the blood culture yielded Staphylococcus aureus and Pseudomonas species. The infant received antibiotics, and the wound was debrided. He was discharged after sixteen days of hospitalization. This case is reported to highlight the possible role of injections under septic conditions as a risk for necrotizing fasciitis in the newborn. Health workers are encouraged to ensure aseptic skin preparation before injections.